Response of Bird Community Toward Tourism Activities in the Karst Area of Bantimurung Bulusaraung National Park. Issue 2 (3rd March 2020) - Putri, Indra A.S.L.P.; Ansari, Fajri; Susilo, Adi
ABSTRACT: Countless birds live in environments that have been modified, to some degree, by human activities. This study aims to determine the response of bird community to tourism activities in the karst area of Bantimurung Bulusaraung National Park. Bird populations were observed and compared under four different circumstances: in the center of tourist activity (A) with a crowd (on weekends) or (B) without visitors (on weekdays), (C) in rarely used sites through which only the local community passes, and (D) in sites rarely visited by tourists. These circumstances represent four different gradients of human presence disturbances. ANOVA, Kruskal–Wallis, and Mann–Whitney were used to compare the differences in the number and composition of bird families, species, individuals, and feeding guilds. Results show a low number of birds in the crowded areas, thereby confirming the impact of human presence on the bird community.